Pembangunan Smart Detection Absensi Berbasis Kartu RFID dan ESP 32 - Fikri Fajar Asshiddiqi; Agung Triayudi; Rima Tamara Aldisa (Universitas Budi Darma, 2022)
In today's era with the rapid development of technology and the development of semiconductor technology, it is possible to create integrated circuits on an increasingly large scale and can integrate many different systems. One of the benefits of current technological developments in the attendance recording tool, whose data is integrated into the learning information system to replace the manual recording model. This tool is designed by integrating the work of a radio frequency identification (RFID) microcontroller into one system. The extracted data as a unique number from the RFID tag is used as student data. After the card is attached to the assessment device, student data will automatically be entered into the attendance database. By making this tool, it can facilitate the work and activities of students and lecturers in conducting lecture activities and also as learning for all in this period of rapid technological development